Survey of educators regarding the return to learn after a sport-related concussion. Issue 11 (25th May 2017) - Carson, James D; Garel, Alisha; Rendely, Alexandra; Meaney, Christopher; Moser, Stefanie E; Rabinovitch, Sarah T; Kraft, Sari A; Fremont, Pierre
Abstract : Objective: To evaluate the impact of an educational intervention upon educators' knowledge of sport-related concussion (SRC) management strategies and their understanding of academic accommodations as part of the return to learn (RTL) strategy after an SRC. Design: A pre- and post-intervention study. Setting: A sport-focused Ontario (Canada) secondary school. Participants: 94 educational staff, including teachers, administrators and school psychologists. Interventions: Three ten-minute didactic lectures were followed by ninety minute facilitated focus groups during an educators' professional development workshop. Participants learned about the nature and management of SRC with an emphasis upon RTL. Participants also had to reflect on their own experiences with some of the 63 students who had RTL at that school, after an SRC during the prior 3.5 years. Outcome measures: Participants answered pre and post intervention surveys directed toward knowledge of SRC management principles and acknowledgement of accommodations. Main results: 81 of the 94 participants submitted two matched pre and post surveys. Educators indicated significantly increased understanding of SRC management and showed a significantly increased support of accommodations after the intervention (p<0.05). Conclusions: Educators' understanding of SRC management strategies is essential to facilitate a successful RTL. This study suggests that a brief educational intervention can improve the support of educators for academic accommodations as part of the RTL phase of SRC management. Competing interests: None.